An algebraic approach to the variants of convexity for soft expert approximate function with intuitionistic fuzzy setting. Issue 1 (31st December 2023) - Ihsan, Muhammad; Saeed, Muhammad; Khan, Khuram Ali; Nosheen, Ammara
Abstract : A new area of research called intuitionistic fuzzy soft expert set is expected to overcome the drawbacks of an intuitionistic fuzzy soft set in terms of eligibility for soft expert-argument approximate function. This type of function views the power set of the universe as its co-domain and the cartesian product of attributes, experts, and their opinions as its domain. The domain of this function is larger as compared to the domain of a soft approximation function. It can manage a situation in which several expert opinions are taken into account by a single model. For the soft expert-argument approximate function with intuitionistic fuzzy setting, concepts such as set inclusion, ( α, v ) -convexity(concave) sets, strongly ( α, v ) -convexity (concave) sets, strictly ( α, v ) -convexity (concave) sets, convex hull, and convex cone are conceived in this paper. Some set-theoretic inequalities are established with generalized properties and results on the basis of these specified notions. Additionally, by using a theoretic cum analytical approach, various elements of computational geometry, such as convex hull and convex cone, are theorized and some pertinent results are generalized.